2022
DOI: 10.1002/glia.24259
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte‐specific loss of lactoferrin influences neuronal structure and function by interfering with cholesterol synthesis

Abstract: Growing evidence indicates that circulating lactoferrin (Lf) is implicated in peripheral cholesterol metabolism disorders. It has emerged that the distribution of Lf changes in astrocytes of aging brains and those exhibiting neurodegeneration; however, its physiological and/or pathological role remains unknown. Here, we demonstrate that astrocyte‐specific knockout of Lf (designated cKO) led to decreased body weight and cognitive abnormalities during early life in mice. Accordingly, there was a reduction in neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Lf is overexpressed in the glial cells and neurons of the elderly person and AD patients (Kawamata et al, 1993;Leveugle et al, 1994), while, to date, the functions of Lf in different cell types remain unexplored. Our recent study exerted that astrocytic Lf knockout impaired the neuronal dendritic complexity and cognitive ability via decreasing cholesterol production during early life in mice (Xu et al, 2022), suggesting the important roles of astrocytes in regulating neuronal functions. Several studies revealed that supplements with Lf effectively retarded AD progression (Abdelhamid et al, 2020;Guo et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lf is overexpressed in the glial cells and neurons of the elderly person and AD patients (Kawamata et al, 1993;Leveugle et al, 1994), while, to date, the functions of Lf in different cell types remain unexplored. Our recent study exerted that astrocytic Lf knockout impaired the neuronal dendritic complexity and cognitive ability via decreasing cholesterol production during early life in mice (Xu et al, 2022), suggesting the important roles of astrocytes in regulating neuronal functions. Several studies revealed that supplements with Lf effectively retarded AD progression (Abdelhamid et al, 2020;Guo et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…The primary astrocytes were extracted according to our previous study with some modifications (Xu et al, 2022). In this study, wild-type (WT) mice and Astro-Lf mice were employed to obtain the primary astrocytes.…”
Section: Primary Astrocyte Culturementioning
confidence: 99%
“…Notably, astrocytic Lf knockout significantly inhibited cholesterol synthesis and reduced APOE expression (Xu et al, 2022), suggesting that Lf overexpression in astrocytes may increase the expression of APOE via modulating cholesterol synthesis. How the astrocytic Lf overexpression promotes APOE up-regulation is an interesting topic, and we hope to uncover the mechanism in our future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Lf is overexpressed in glial cells and neurons of elderly people and AD patients (Kawamata et al, 1993; Leveugle et al, 1994), although, to date, the functions of Lf in different cell types remain largely unexplored. Astrocytic Lf knockout impaired neuronal dendritic complexity and cognitive ability, by decreasing cholesterol production during early life in mice (Xu et al, 2022), suggesting important roles for astrocytic Lf in regulating neuronal functions. In this study, human Lf overexpression in astrocytes improved the cognitive capacity of APP/PS1 mice and also improved the vision of WT mice, possibly via enhanced brain development caused by Lf‐induced up‐regulation of neuronal connectivity and neurotrophin production (Chen et al, 2015; Schirmbeck et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation